Arab Pra-Islam (Sistem Politik Dan Kemasyarakatan Sistem Kepercayaan Dan Kebudayaan) - Anjar Fikri Haikal; Mahmudah Mahmudah; Kholid Mawardi (Departement of Mathematics Education, 2023)
Jahiliyah is a term given to Arab society that refers to the period of time and conditions in Arab lands before the arrival of Islam in 610 AD. The word jahiliyah is translated as